Juvenile psammomatoid ossifying fibroma - Radzki, Dominik; Szade, Jolanta; Nowicki, Tomasz; Biernat, Wojciech (Polish Journal of Pathology, 2021)
Juvenile psammomatoid ossifying fibroma (JPOF) is an uncommon benign and locally aggressive tumor. We report an unusual head tumour with extremely rare extensiveness and aggressivness. The patient was 18-year-old female with three-day-lasting headache and repetitive oral bleeding. Computed tomography revealed a large, well-circumscribed, expansile mass occupying ethmoid cells, nasal cavities and ventral part of the sphenoid sinus, with extention into the anterior cranial fossa. Pterional craniotomy was carried out. On one-year follow-up recurrence of the lesion was identified and the second surgery was performed. The lesion is under supervision now, due to incomplete removal.